2021
DOI: 10.3390/app11135977
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Ternary Cements Based on New Supplementary Cementitious Materials from Industrial Waste

Abstract: Cement-based materials decay with exposure to aggressive agents, a development that raises infrastructure operation and maintenance costs substantially. This paper analyses the inclusion of ultrafine construction and demolition (UC&DW) and biomass-fuelled power plant (BA) waste as pozzolanic additions to cement in pursuit of more sustainable and eco-respectful binders and assesses the durability of the end materials when exposed to seawater, chlorides (0.5 M NaCl) or sulphates (0.3 M Na2SO4). The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that concrete containing mineral admixtures is significantly more resistant to chlorides and other agents that cause degradation [14,21]. To a large extent, it is influenced by a small number of criteria, including the manner in which the minerals react with the oxides during the hydration stage, the nature of the chlorides and the effects that they have [16,58,60]. As a consequence of these factors, the strength of mortar that contains BA can be affected negatively if it is exposed to a chloride environment.…”
Section: Durability Testmentioning
confidence: 99%
“…It has been demonstrated that concrete containing mineral admixtures is significantly more resistant to chlorides and other agents that cause degradation [14,21]. To a large extent, it is influenced by a small number of criteria, including the manner in which the minerals react with the oxides during the hydration stage, the nature of the chlorides and the effects that they have [16,58,60]. As a consequence of these factors, the strength of mortar that contains BA can be affected negatively if it is exposed to a chloride environment.…”
Section: Durability Testmentioning
confidence: 99%